Match demands of elite preadolescent team handball players: a preliminary study - Foretic, N.; Uljevic, O.; Cardinale, M.; Spasic, M. (Medicina dello Sport, 2018)
BACKGROUND: The aim of study was to examine the acute physiological responses and their relationship with physiological characteristics of preadolescent male handball players. METHODS: Laboratory testing included anthropometric measurements and spiroergometry. Time motion analysis data were obtained through recording of player`s game activities and later analyzed with a bespoke software package developed with Matlab. Heart Rate data was recorded with chest straps. Blood samples were collected at 5 predetermined time points over the course of 2 matches. RESULTS: T-test and Pearson product moment correlation coefficient was used to examine the differences and the relationship between variables collected in the study. Time motion analysis did not show significant differences between the total distance covered by players in the first (2220.50±162.85 meters) and in the second (2131.42±239.80 meters; Cohen`s d=0.43) half of the match; however the effect size was small to moderate. A significant moderate relationship between blood lactate at the end of the second half and the difference in the distance covered between 2nd and 1st half (r=0.50, P<0.05) was identified and a large relationship between blood lactate measured in the second half and the reduction in speed (r=0.75, P<0.05). The results of this study suggest that aerobic capacity in this group of athletes could not explain the total distance covered during a handball game. CONCLUSIONS: The study also showed that the demands of playing handball at this age are different from adult competitors possibly due to technical and tactical abilities.